Female types in V.P. Meshchersky's publicistic and fictional works - Yu.B. Avdonina; G.I. Shcherbakova (Ученые записки Казанского университета: Серия Гуманитарные науки)
Female types in the publicistic and fictional works of V.P. Meshchersky (1839–1914), the publisher and editor of the “Grazhdanin” journal and the same-named newspaper, have been analyzed. The influence of romanticist and realistic principles, aesthetic and moral principles has been identified. The role of the conservative ideology supported by V.P. Meshchersky has been determined. The paper discusses the half-forgotten works of the author that were published in the 1870s and have not been reprinted for a long time. These works are “Women of St. Petersburg's Haut Monde” (1874–1879), “Notes of a High-School Student Who Shot Himself” (1875), “Conventionalist's Speeches” (1876), “Secrets of Contemporary St. Petersburg” (1876–1877), “Caucasian Travel Diary” (1878), “Petya Skuratov” (1878), etc. As a result of the study, the following types have been singled out in the system of female images: angel women, a loyal friend and faithful helper; noble woman, in particular a socialite longing for being totally worshiped; selfish nihilist forgotten about her natural mission; reclaimed woman who turned to the Christian patriarchal traditions. In our opinion, the objective scientific analysis without permitting the influence of any political ideology makes it possible to understand V.P. Meshchersky's position and to estimate his contribution in the history of Russian journalism, literature, and social movements.